RITUS KOMUNI DAN RITUS PENUTUP: ANALISIS TEOLOGIS DAN REFLEKSI SEJARAH TATA PERAYAAN EKARISTI - Ian Jovi Sianturi; Kevin Hendrarto Tandautama; Freddy Fransiskus Situmorang; Hendrikus Rinaldi Amsikan; Rafael Makul (Aggiornamento, 2023)
This study is a theological analysis and historical reflection on Tata Perayaan Ekaristi (TPE) 2020. Although welcomed by the Indonesian Church, new changes always raise new problems. This is the background of the search for the historical and theological rites in it. This study examines the following: (1) the existence of the Communion Rite and Closing Rite in historical and theological contexts, (2) reflections on the translation of the Communion Rite to the Closing Rite in TPE 2005 and TPE 2020. The method used is literary studies from various sources. liturgy and history with a liturgical science approach. This study pays attention to the text Editio Typica, Ordo Missae 2008 and its translations in TPE 2005 and TPE 2020. This description does not intend to cause new controversy, but presents matters relating to the historical context, rites, theology and translations. From this description, it is found that there are translations that seem rigid and literal, but there are also those that enrich or clarify their theological meanings.